'Like second-hand smoke': the toxic effect of workplace flexibility bias for workers' health. Issue 5 (20th October 2017) - Cech, Erin A.; O'Connor, Lindsey Trimble
ABSTRACT: As many workers struggle to reconcile their personal and work responsibilities, scholars have called on organizations to redesign and redefine workplace structures and cultures. One pernicious feature of today's organizations is workplace flexibility bias, workers' sense that they will face career consequences for making schedule adjustments for family or personal reasons. Expanding the theoretical and empirical understanding of this bias, we ask whether and how flexibility bias affects workers' health. Analysis of 2008 National Study of the Changing Workforce data shows that workplace flexibility bias is related to minor health problems, poor self-rated health, poor sleep quality, depression symptoms, and more frequent sick day use. Mediation analysis illustrates that this is due in part to the increased stress and negative work-life spillover that accompanies flexibility bias. This bias is also linked to alcohol use, exercise frequency, and treatment for high blood pressure and mental health issues indirectly via stress and spillover. Importantly, these deleterious effects are net of caregiving responsibilities and flexible work arrangement use, suggesting that current workplace structures and cultures are not just problematic for workers with family responsibilities but can make all types of workers sick. These results help provide more compelling scholarly and business cases for work redesign and redefinition.